5-3x+2=4x+7

Simple and best practice solution for 5-3x+2=4x+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-3x+2=4x+7 equation:


Simplifying
5 + -3x + 2 = 4x + 7

Reorder the terms:
5 + 2 + -3x = 4x + 7

Combine like terms: 5 + 2 = 7
7 + -3x = 4x + 7

Reorder the terms:
7 + -3x = 7 + 4x

Add '-7' to each side of the equation.
7 + -7 + -3x = 7 + -7 + 4x

Combine like terms: 7 + -7 = 0
0 + -3x = 7 + -7 + 4x
-3x = 7 + -7 + 4x

Combine like terms: 7 + -7 = 0
-3x = 0 + 4x
-3x = 4x

Solving
-3x = 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3x + -4x = 4x + -4x

Combine like terms: -3x + -4x = -7x
-7x = 4x + -4x

Combine like terms: 4x + -4x = 0
-7x = 0

Divide each side by '-7'.
x = 0

Simplifying
x = 0

See similar equations:

| 4x^2-23x+13=-7x+6 | | 24-6m=0 | | .5(10z+8)-2=4(z-6) | | 8+9x=-6 | | 2(x+3)=5+2x | | x/3+4=x/6+2 | | 5x+35=7(x+5)-2x | | 6x+3(1+3x)=3+15x | | 3x^6+192=0 | | 2x+24=4(x+6)-2x | | -9-6k+9-(-2k)= | | (2x+4)+(2x+-9)+x=180 | | (w-5)(w-5)=2w^2-6w+28 | | 8+12k-8k-5k= | | x^2-4x-44=3x-6 | | x^2-7x-38=0 | | 8x+34= | | 5y-4=2y+23 | | 9ln(7x)=72 | | 3(-2)=-9y+33 | | 10k+7-3k-11= | | 5x-8y-15=0 | | 3x=-9(6)+33 | | 3(5)=-9y+33 | | 8a-1.5=3a-7 | | 3y-12=4y+88 | | C=50(215)+40 | | 1.5=50n+40 | | 2=50n+40 | | T=L(4+RS) | | 5(x-3)+4=2(x-4) | | 12x^2+17x-7=0 |

Equations solver categories